Peran Guru Bimbingan dan Konseling Dalam Membentuk dan Meningkatkan Nilai dan Moral Siswa di Sekolah - Salimatul Islamiyah; Eka Susanti; Annisa Nurul Fadilah; Amelia Sri Muliani; Melisa Febriani; Dinda Aulia; Bunaisah Saragih; Fitri Nurazizah; Faisal Akbar; Rizky Ramadhan Damanik (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
His study examines the role of guidance and counseling teachers in shaping and improving student values and morals in school. The study aims to investigate the impact of guidance and counseling on students' moral development and the strategies used by teachers to promote moral values. The research employed a mixed-methods approach, combining both quantitative and qualitative data collection and analysis methods. The results show that guidance and counseling teachers play a significant role in fostering moral values and ethics among students. The study highlights the importance of teacher-student relationships, classroom management, and the use of various teaching strategies in promoting moral development. The findings also suggest that guidance and counseling teachers should be equipped with the necessary skills and resources to effectively address the moral needs of students. The study concludes that the role of guidance and counseling teachers in forming and enhancing student values and morals is crucial in creating a positive and supportive learning environment.